2022
DOI: 10.1039/d2sc02446b
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide mapping of N4-methylcytosine at single-base resolution by APOBEC3A-mediated deamination sequencing

Abstract: N4-methylcytosine (4mC) is a natural DNA modification occurring in thermophiles and plays important roles in restriction-modification (R-M) systems in bacterial genomes. However, the precise location and sequence context of 4mC...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Previous studies reported that APOBEC3 family proteins can deaminate cytosine to form uracil in DNA. , Along this line, we demonstrated that APOBEC3A (A3A) could efficiently deaminate cytosine and 5mC but not N 4 -methylcytosine (4mC) . By virtue of this unique property of the A3A protein, we developed an APOBEC3A-mediated deamination sequencing (4mC-AMD-seq) method for mapping 4mC at the single-base resolution .…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Previous studies reported that APOBEC3 family proteins can deaminate cytosine to form uracil in DNA. , Along this line, we demonstrated that APOBEC3A (A3A) could efficiently deaminate cytosine and 5mC but not N 4 -methylcytosine (4mC) . By virtue of this unique property of the A3A protein, we developed an APOBEC3A-mediated deamination sequencing (4mC-AMD-seq) method for mapping 4mC at the single-base resolution .…”
Section: Resultsmentioning
confidence: 83%
“…25,26 Along this line, we demonstrated that APOBEC3A (A3A) could efficiently deaminate cytosine and 5mC but not N 4methylcytosine (4mC). 27 By virtue of this unique property of the A3A protein, we developed an APOBEC3A-mediated deamination sequencing (4mC-AMD-seq) method for mapping 4mC at the single-base resolution. 27 However, A3A could not distinguish cytosine and 5mC.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that A3A protein could efficiently deaminate C and 5mC in DNA to form U and T, respectively. , However, the oxidative derivative of 5mC, i.e., 5-carboxylcytosine (5caC), was resistant to deamination by A3A due to the presence of the carboxy group in 5caC . On the other hand, one recent study found that the mutant of CG-specific methyltransferase M.MpeI, i.e., M.MpeI-N374K, can specifically transfer a carboxymethyl group from caSAM to cytosine to form 5camC.…”
Section: Resultsmentioning
confidence: 99%
“…Resistance of 4mC to enzymatic deamination by APOBEC3A (4mC‐AMD‐seq) was used to discriminate 4mC from C and 5mC in the radioresistant bacterium Deinococcus radiodurans . [ 66 ] This method avoids excessive DNA degradation and can be applied to low‐input samples. Further improvement of 4mC detection methods in eukaryotes will be essential for establishment of validated 4mC reference datasets for training of bioinformatic pipelines, and for eventual elucidation of its biological functions.…”
Section: Methodological Challenges In Identifying Non‐canonical Base ...mentioning
confidence: 99%